2005
DOI: 10.1007/s10812-005-0091-8
|View full text |Cite
|
Sign up to set email alerts
|

Manifestations of Phase Transitions and the Thermooptical-Memory Effect in the Absorption Spectra of (N(CH3)4)2CuCl4 Crystals

Abstract: The manifestations of phase transitions and the spatial modulation of the structure of the (N(CH 3 ) 4 ) 2 CuCl 4 crystal in its absorption spectra have been investigated. It has been established that the thermooptical-memory effect manifesting itself in the absorption spectra of this crystal entirely corresponds to the model of ordering of defects and impurities in a sample with a modulated structure. It is shown that, as a result of stabilization of the crystal studied in the incommensurate phase, its symmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The physical properties of [N(CH 3 ) 4 ] 2 ZnCl 4 and [N(CH 3 ) 4 ] 2 CuCl 4 have been studied using various experimental methods by several research groups. [11][12][13][14][15][16][17][18][19][20] Ribet et al 21 reported observing ferroelectric-ferroelastic phase transitions of [N(CH 3 ) 4 ] 2 ZnCl 4 through X-ray and synchrotron topography. Recently, the roles of chemically inequivalent a-N(CH 3 ) 4 and b-N(CH 3 ) 4 ions in [N(CH 3 ) 4 ] 2 ZnCl 4 and [N(CH 3 ) 4 ] 2 CuCl 4 have been reported by static nuclear magnetic resonance (NMR) and magic angle spinning (MAS) NMR, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The physical properties of [N(CH 3 ) 4 ] 2 ZnCl 4 and [N(CH 3 ) 4 ] 2 CuCl 4 have been studied using various experimental methods by several research groups. [11][12][13][14][15][16][17][18][19][20] Ribet et al 21 reported observing ferroelectric-ferroelastic phase transitions of [N(CH 3 ) 4 ] 2 ZnCl 4 through X-ray and synchrotron topography. Recently, the roles of chemically inequivalent a-N(CH 3 ) 4 and b-N(CH 3 ) 4 ions in [N(CH 3 ) 4 ] 2 ZnCl 4 and [N(CH 3 ) 4 ] 2 CuCl 4 have been reported by static nuclear magnetic resonance (NMR) and magic angle spinning (MAS) NMR, respectively.…”
Section: Introductionmentioning
confidence: 99%